2011
DOI: 10.1038/cmi.2011.50
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-presenting effects of effector memory Vγ9Vδ2 T cells in rheumatoid arthritis

Abstract: Rheumatoid arthritis is an autoimmune disease that primarily affects the limbs, but the pathogenic mechanism remains unclear. cd T cells, a T-cell subpopulation, are characterized by multiple biological functions and associated with a variety of diseases. This study investigated the antigen-presenting effects of cd T cells and their relationship with rheumatoid arthritis development. We found that Vc9Vd2 T cells (the predominant subtype of cd T cells in peripheral blood) were activated by isopentenyl pyrophosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 33 publications
4
40
0
1
Order By: Relevance
“…Using (57,58), arthritis (59)(60)(61)(62), and inflammatory bowel disease (63), stimulating functions of gd T cells on CD4 + T cells and inflammation have been reported. gd T cells functioned as APCs, enhancing CD4 + T cell activation (55,56), or promoted differentiation of naive T cells into autoreactive Th17 cells while inhibiting peripheral Tregs (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Using (57,58), arthritis (59)(60)(61)(62), and inflammatory bowel disease (63), stimulating functions of gd T cells on CD4 + T cells and inflammation have been reported. gd T cells functioned as APCs, enhancing CD4 + T cell activation (55,56), or promoted differentiation of naive T cells into autoreactive Th17 cells while inhibiting peripheral Tregs (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…As such, these 'Vc9/Vd2 TAPCs' are capable of inducing MHC class II restricted CD4 + T cell responses upon presentation of the staphylococcal superantigen toxic shock syndrome toxin 1 (TSST-1) that crosslinks HLA-DR on the APC surface with the TCR of responder cells carrying a Vb2 chain, and in mixed lymphocyte responses as a reaction to donor mismatched MHC class II alleles [116]. Moreover, Vc9/Vd2 T-APCs have also been shown to induce antigen-specific CD4 + T cell responses upon direct presentation of antigenic peptides or upon uptake and intracellular processing of microbial antigens like M. tuberculosis PPD and tetanus toxoid [116,123].…”
Section: Priming Of Cd4 + and Cd8 + T Cells By Vc9/vd2 T Cells: A Newmentioning
confidence: 99%
“…Indirect support for a possible role as APC stems from observations that HLA-DR is expressed by activated Vc9/Vd2 T cells in patients with severe inflammation or during acute infection [123,[138][139][140], and in patients receiving intravenous zoledronate with and without 141,142]. However, functional evidence into the potential of activated Vc9/Vd2 T cells to act as APC ex vivo is only beginning to emerge [123,143]. NKT cells are a heterogeneous group of T cells that share properties of both T cells and NK cells [144][145][146].…”
Section: Priming Of Cd4 + and Cd8 + T Cells By Vc9/vd2 T Cells: A Newmentioning
confidence: 99%
See 1 more Smart Citation
“…In oligoarticular JIA a specific subset of γδ-T cells (Vδ1+Vγ9+) was associated with milder disease but they did not study the total γδ-T cells or IL-17 production by them [35]. Recent study on RA has revealed that the PB and SF γδ-T cells, on stimulation with isopentenyl pyrophosphate (IPP) secrete more IL-17 [36]. Hence in ERA γδ-T cells may act as a source of IL-17 and perpetuate inflammation.…”
Section: Discussionmentioning
confidence: 96%